MODEL MANAJEMEN KOMUNIKASI DAN ADMINISTRASI BACK OFFICE E-GOVERNMENT SEBAGAI MEDIA PELAYANAN PUBLIK - Sosiawan, Edwi Arief; Pujiastuti, Eny Endah (Jurnal Ilmu Komunikasi, 2009)
On the challenges of development for democratization and transparency in the frame- work of regional autonomy, local governments now compete to build a race-e-government infrastructure. In factual, the main obstacles of the implementation of e-government is on the governance or management structure of the management and quantity and quality of human resources at government agencies that are very limited. The object of the selected study site is The City of Yogyakarta and The Sleman regency government. The formulation of the problem is taken “How E-Government Communication and Adminitrations Management Back Office Models as a Public Service Studies on the regional government of Yogyakarta and Sleman District Government Sites? “ Research method used was descriptive research to guide the inductive eksploratory to the results of research that the technical provisions of the respective websites of local governments to become the object of research in managing the front office has to follow some standard that is required in the development of the web as a medium for communication and information. Information uptodating, especially news on the navigation was done routinely. But still there is a delay of uptodating websites is a sign that there is imbalance between the management of websites each local government. Number of links the information of each local government websites have been sufficient, meaning that many categories of information provided. The fundamental problem lies in the fact that the government does not provide e-mail links for the user community, if there is acceptance of the feedback is to the manager or administrator websites and not on the officials concerned.